Prevalence of low birth weight in a scenario of economic depression in Argentina - Ratowiecki, Julia (2018)
Introduction. Low birth weight (LBW) is considered a general indicator of health because it is related to complications in the life of a newborn infant and is one of the leading causes of infant mortality. It is a multifactorial indicator, and its determinants include socioeconomic factors. Objective. To assess the impact of economic inequality on the prevalence of LBW by quantifying its differential effect by maternal age, level of maternal education, and level of care. Population and methods. Epidemiological, cross-sectional study that analyzed all births occurred in Argentina between 2001 and 2013 based on data provided by the National Registry of births, corresponding to the Health Statistics and Information Department. The temporal variation in the prevalence of LBW newborn infants (< 2500 grams) and its relation to demographic and socioeconomic indicators were studied. Its association was assessed using logistic regression models. Results. A total of 9 001 960 births were included. The prevalence of LBW newborn infants during the 2001 economic crisis increased -6% in 2002 and 7% in 2003- The impact was heterogeneous and higher on public hospitals ([PR] = 1.03) and adolescent mothers (PR = 1.07), but no impact was observed on a low level of maternal education (PR= 0.99). Conclusions. The impact of socioeconomic inequality on the prevalence of LBW was significant and heterogeneous, especially on public hospitals and mothers at the extremes of maternal age.